2017
DOI: 10.1159/000449528
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Underlying the Inhibitory Mechanism of Fluoxetine on Electrical Field Stimulation Response in Rat Ileal Smooth Muscle

Abstract: Fluoxetine (FLX), a well-known antidepressant drug under the class of selective serotonin reuptake inhibitor, exerts its action by inhibiting the reuptake of serotonin selectively. In some studies, it has been demonstrated that FLX relaxes the intestinal smooth muscle. In this study, we aimed at studying the signal transduction pathway underlying the muscle relaxation effect of FLX on electrically stimulated rat ileal muscle contraction. To investigate the possible mechanism involved, various antagonists were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition to inhibition of serotonin reuptake that is common to all SSRIs, some of these antidepressants also have other effects, primarily at the level of smooth muscle cells and specificity of these effects is predominantly the result of significant differences in their chemical structures . The studies conducted on animal models have shown that fluoxetine causes dilatation of cerebral arterioles and skeletal muscle arterioles, as well as inhibition of the potassium‐induced contraction of the isolated uterine artery .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to inhibition of serotonin reuptake that is common to all SSRIs, some of these antidepressants also have other effects, primarily at the level of smooth muscle cells and specificity of these effects is predominantly the result of significant differences in their chemical structures . The studies conducted on animal models have shown that fluoxetine causes dilatation of cerebral arterioles and skeletal muscle arterioles, as well as inhibition of the potassium‐induced contraction of the isolated uterine artery .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that SSRIs relax intestinal smooth muscle cells . It is believed that SSRIs primarily achieve these effects acting on voltage‐dependent channels for sodium (Na + ), potassium (K + ) and calcium (Ca 2+ ) ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation